EVALUASI SISTEM KOMPENSASI BERBASIS METODE POIN FAKTOR PADA UKM XYZ - Lindawati Kartika; Fitroh Agung Dimas Tetuko; Kharismatul Zaenab Akhilla; Feni Apriyani; Alda Savana; Naufal Rafif Ramadhan (CV. Multi Kreasi Media, 2023)
An effective compensation system plays an important role in human resource management because it can help attract and retain employees who perform their jobs well. A good compensation system for SMEs can be measured by the compensation provided, while paying attention to the District/City Minimum Wage (UMK) and Provincial Minimum Wage (UMP) in each region. The research object of this journal is XYZ UKM, which is a UKM engaged in the field of Food and Beverage. With the distinctive taste of tea connoisseurs and customer-friendly service, XYZ UKM sells contemporary beverage products with a variety of flavors and affordable prices. The purpose of this research is to identify the condition of the compensation system that is applied, identify compensable factors to be analyzed, and analyze the ideal compensation system. Primary data collection techniques include direct interviews with three leaders and the distribution of questionnaires to company employees. This research is a quantitative and qualitative study, describing and evaluating the compensation system implemented at PT XYZ with the eckenrode method.